Beyond the barriers: An overview of mechanisms driving barriers to adaptation in Bangladesh. (27th November 2020) - Ishtiaque, Asif; Stock, Ryan; Vij, Sumit; Eakin, Hallie; Chhetri, Netra
Abstract: Climate change adaptation governance involves multiple actors, operating from local to national level, and during their interactions, several challenges may surface and act as barriers to adaptation. While existing studies attempted to create an exhaustive list of barriers by focusing on "what" is occurring, we continue to have a meager understanding of "how" or "why" barriers emerge in the governance process. Selecting Bangladesh as a case study area, we identify the mechanisms that cause the emergence of barriers in the climate change adaptation governance process. We particularly focus on the barriers that emerge through interactions among actors. We base our research on data from key‐informant interviews and a systematic literature review. Our analysis reveals that there are at least five mechanisms that are involved in the emergence of barriers: enclosure and exclusion, boundary control, organizational inertia, belief formation, and frame polarization. Our identification of common mechanisms provides insights on actors' roles and activities in adaptation governance and elucidates the processes through which actors' interactions lead to barriers. This mechanism‐based analysis of barriers will help to address and navigate through the barriers more effectively to ensure successful adaptation. As climate change is becoming mainstreamed in development plans and policies in our study area, identifying the mechanisms of adaptation barriers can elucidate how development and climate adaptation strategies are affected by identified barriers.